Doses de lodo de esgoto compostado em produção de tapete de grama esmeralda imperial - Backes, Clarice; Santos, Alessandro José Marques; Godoy, Leandro José Grava de [UNESP]; Villas Boas, Roberto Lyra [UNESP]; Oliveira, Maurício Roberto De; Oliveira, Fernando Carvalho De (Sociedade Brasileira de Ciência do Solo, 2013)
The efficiency of nitrogen fertilization for sod production can be increased by using slow-release sources such as sewage sludge compost, which, due to its characteristics can be a substitute of part or all inorganic fertilization for grass. No results were found for the use of sludge compost in sod production in Brazil. This study evaluated the effect of rates of sewage sludge compost on the production of zoysiagrass. Treatments consisted of five rates of composted sewage sludge compost (0, 12, 24, 36 and 48 Mg ha-1, on a dry basis), plus a treatment of inorganic fertilization (300 kg ha-1 N, 80 kg ha-1 P2O5, and 200 kg ha-1 K2O). The results indicated different mineralization rates of the organic compounds present in the sludge; 120 days after sludge application, more Mg (100 %), K (90 %) and N (67 %) has been released than S (57 %), P (40 %) and Ca (31 %). The use of composted sewage sludge for zoysiagrass adequately supplied nutrients when applied to the soil surface at rates more than 36 Mg ha-1. After sod cutting, the rates of sewage sludge compost provided a linear increase in potential soil acidity, soil contents of OM, P, S, Fe, Cu, Mn, Zn, Cu and Ni, and linear decrease in pH, soil concentration of Ca and Mg and base saturation. Compost rates, increasing from 0 to 48 Mg ha-1, reduced the sod mass, reaching values of 4.0 kg/sod at the highest rate. High compost doses (36 and 48 Mg ha-1, respectively) also induced the highest resistance, with values in the order of 35 and 33 kgf.

A eficiência da adubação nitrogenada para gramados pode ser aumentada com a utilização de fontes de liberação lenta, como composto de lodo de esgoto, que, em razão das suas características, pode ser um substituto de parte ou do total da adubação inorgânica para as gramas. Não foram encontrados resultados referentes à utilização de lodo compostado na cultura da grama, no Brasil. Objetivou-se com este trabalho avaliar o efeito de doses de composto de lodo de esgoto na produção da grama esmeralda Imperial. Os tratamentos foram constituídos de cinco doses de composto de lodo de esgoto (0, 12, 24, 36 e 48 Mg ha-1, base seca), mais um tratamento com adubação inorgânica (300 kg ha-1 N, 80 kg ha-1 P2O5 e 200 kg ha-1 K2O). Os compostos orgânicos presentes no composto têm diferentes taxas de mineralização, liberando aos 120 dias após a aplicação do lodo mais Mg (100 %), K (90 %) e N (67 %) do que S (57 %), P (40 %) e Ca (31 %). A utilização do composto de lodo na cultura da grama Imperial proporcionou adequado fornecimento de nutrientes, quando aplicado superficialmente, em doses maiores que 36 Mg ha-1. As doses de composto proporcionaram, após a colheita do tapete, aumento linear da acidez potencial e do teor de matéria orgânica, P, S, Fe, Cu, Mn, Zn, As, Cu e Ni e redução linear do pH, do teor de Ca e Mg e da saturação por bases do solo. O aumento das doses do composto de 0 a 48 Mg ha-1 reduziu a massa dos tapetes de grama, atingindo valores de 4,0 kg/tapete, quando a maior dose foi aplicada. Altas doses também proporcionaram os maiores valores de resistência dos tapetes na ordem de 35 e 33 kgf, com as doses de 36 e 48 Mg ha-1, respectivamente.
Rates of sewage sludge composted in the zoysiagrass sod production
Keywords: gramado; adubação; nitrogênio; grass sod; fertilization; nitrogen